Silicon‐containing polyarylacetylene aerogel with heat resistance and ablative property for high‐temperature insulation. Issue 25 (15th April 2022) - Zhao, Chuanqing; Chen, Fan; Dong, Sensen; Liu, Xiaoyun; Qi, Huimin; Deng, Shifeng
Abstract: Owing to the high porosity and low thermal conductivity of organic aerogels, they have been widely used to develop lightweight heat insulation materials. However, their applications in high‐temperature environments such as in aerospace applications are usually limited by the heat resistance or ablative property of the organic matrix. In this study, we prepared a novel organic aerogel for high‐temperature insulation by the sol–gel method and freeze‐drying. The matrix is the thermosetting silicon‐containing polyarylacetylene (PSA) resin with excellent comprehensive properties, namely, high heat stability, low volatile component content, and high‐temperature ceramic performance. The obtained PSA aerogel retains the heat resistance (Td5 = 634.8°C) and ablative properties (Yr800 = 92.6%) of the PSA resin, and the internal regular macropores and high porosity (70%) result in an extremely low weight (0.1200 g cm −3 ), low thermal conductivity (0.039 W m −1 K −1 )), and efficient heat insulation. Thus, this is an ideal material for high‐temperature insulation in the aerospace field. Abstract : The thermal conduction of PSA aerogel consists of three parts: gas thermal conduction, solid thermal conduction and radiation heat transfer. The high porosity reduces the solid thermal conduction to have a low thermal conductivity.